2022
DOI: 10.3389/fpubh.2022.878243
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Energy Productivity and Eco-Innovation on Sustainable Environment in Emerging Seven (E-7) Countries: Does Institutional Quality Matter?

Abstract: Emerging economies are showing promising growth and economic success, but the growth process has significantly increased carbon emissions in these countries and deteriorated environmental quality. Environmental degradation is an issue of serious concern as it is directly linked to human lives and health. Since the creation of the Sustainable Development Goals (SDGs), the Emerging Seven (E-7) countries have struggled to meet the SDG targets, as it's been a challenge for them to lower carbon emissions and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…This means that the effectiveness of the implementation of the LCCP policy depends not only on the region where it is implemented but also on the strength of its implementation. Safi et al (2022a) also revealed that policies aimed at institutional quality, ecological innovation and energy productivity significantly affected CO2 emissions and contributed to improving environmental quality.…”
Section: Heterogeneity Of Environmental Regulation Intensitymentioning
confidence: 99%
“…This means that the effectiveness of the implementation of the LCCP policy depends not only on the region where it is implemented but also on the strength of its implementation. Safi et al (2022a) also revealed that policies aimed at institutional quality, ecological innovation and energy productivity significantly affected CO2 emissions and contributed to improving environmental quality.…”
Section: Heterogeneity Of Environmental Regulation Intensitymentioning
confidence: 99%
“…Therefore, it is crucial for governments to focus on ecological tourism policies and energy resources to reduce carbon emissions and promote sustainable development. Carbon emissions are the primary factor in environmental degradation and are related to climate change and global warming, placing environmental sustainability at risk [53]. Reducing the ecological footprint, CO 2 and greenhouse gas emissions, and exposure to air pollution through promoting innovation, improving trade policies, fostering political and legal institutions, and promoting renewable energy are effective ways to address environmental sustainability [54].…”
Section: The Impact Of Carbon Emissions On the Ecological Environmentmentioning
confidence: 99%
“…Similarly, Shahbaz et al (2020) found that introducing energy innovations and energy-efficient technology can have an impact on environmental sustainability. Safi et al (2022) underlined the importance and significance of ecoinnovation in lowering carbon emissions in China. Similarly, Zhang (2023) stressed that eco-innovation can lower CO2 emissions and enhance environmental sustainability when combined with technological breakthroughs.…”
Section: Review Of the Literature On Eco-innovation And Co2 Emissionsmentioning
confidence: 99%
“…Extensive research has consistently shown the significance of this characteristic. Several studies, including Ali et al (2021), Safi et al (2022), Chi et al (2021), and Ameyaw and Yao (2018), have emphasized the importance of technological advancements in reducing emissions and optimizing resource use. The implementation of renewable energy sources has been shown to significantly reduce greenhouse gas emissions and enhance air quality in countries that have made substantial investments in these technologies (Wang et al 2020;Li et al 2020;Kirikkaleli et al 2021).…”
Section: Theoretical Justification and Elaboration Of The Econometric...mentioning
confidence: 99%